MAPK Activated Protein Kinase 3 Is a Prognostic-Related Biomarker and Associated With Immune Infiltrates in Glioma - Ren, Jing; Sun, Jinmin; Li, Mengwei; Zhang, Zifan; Yang, Dejun; Cao, Haowei (Frontiers in Oncology, 2021)
Glioma is the most common primary brain tumor that causes significant morbidity and mortality. MAPK activated protein kinase 3 (MAPKAPK3/MK3) is a serine/threonine protein kinase regulating various cellular responses and gene expression. However, the role of MK3 in tumor progress, prognosis, and immunity for glioma remains unclear. Here, we determined the expression and prognostic values of MK3. We further analyzed the correlation of MK3 expression with immune infiltrations by using the biochemical methods and bioinformatic approaches with available databases. We find that MK3 is aberrantly upregulated in glioma. In addition, the higher MK3 expression is closely linked to the poor clinicopathologic features of glioma patients. Importantly, MK3 expression is negatively correlated with the prognosis of patients with glioma. Mechanistically, we demonstrated that the correlated genes of MK3 were mainly enriched in pathways that regulate tumor immune responses. The MK3 level was significantly associated with tumor-infiltrating immune cells and positively correlated with majority of tumor immunoinhibitors, chemokines, and chemokine receptors in glioma. Thus, these findings suggest the novel prognostic roles of MK3 and define MK3 as a promising target for glioma immunotherapy.